2022
DOI: 10.3390/math10163026
|View full text |Cite
|
Sign up to set email alerts
|

Tail Index Estimation of PageRanks in Evolving Random Graphs

Abstract: Random graphs are subject to the heterogeneities of the distributions of node indices and their dependence structures. Superstar nodes to which a large proportion of nodes attach in the evolving graphs are considered. In the present paper, a statistical analysis of the extremal part of random graphs is considered. We used the extreme value theory regarding sums and maxima of non-stationary random length sequences to evaluate the tail index of the PageRanks and max-linear models of superstar nodes in the evolvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 50 publications
(41 reference statements)
1
14
0
Order By: Relevance
“…Thus, the mentioned pair-wise dependency is not required. The results of the empirical study in [19] are in agreement with theoretical results in [14,15].…”
Section: Network Communities As "Row" Series Of a (0)supporting
confidence: 85%
See 4 more Smart Citations
“…Thus, the mentioned pair-wise dependency is not required. The results of the empirical study in [19] are in agreement with theoretical results in [14,15].…”
Section: Network Communities As "Row" Series Of a (0)supporting
confidence: 85%
“…Using a simulation study, it was found in [19] that the tail indices of the sums and maxima over communities are close to the minimum tail index of the representative series extracted from the communities. The representative series can be formed by taking one of the nodes of a community as a representative.…”
Section: Network Communities As "Row" Series Of a (0)mentioning
confidence: 87%
See 3 more Smart Citations